수분함량에 따른 반건조 우리밀 국수의 품질 특성 - 박복희; 박양균; 조광호; 전은례; 고경미; 최용범; Bock-Hee Park; Yang-Kyun Park; Kwang-Ho Jo; Eun-Raye Jeon; Kyeong-Mi Koh; Yong-Beom Choi (Journal of the Korean Society of Food Culture, 2017)
This study evaluated the quality characteristics of semi-dried noodles prepared with different water contents (wet noodles; 32, 24, 22, 20%, dry noodles; 12%). The drying process was carried out in a drying chamber at 13~18oC temperature and 75~95% humidity. The proximate composition of Korean wheat flour was as follows: water 22.1±3.64%, protein 8.6±0.13%, fat 1.3±0.10%, ash 0.7±0.02%, carbohydrates 67.3±0.10%. As water contents decreased, both L and b values significantly decreased before cooking of noodles, whereas L, a, and b values were not significantly different after cooking of noodles. Weight, water absorption, and volume of cooked noodles significantly increased as water content decreased, whereas turbidity of soup was not significantly different. Cutting hardness before cooking of noodles significantly increased as water content decreased. Sections of noodles after cooking by SEM (scanning electron microscopy) showed roughness and fewer round starch particles as water content decreased. For overall preferences according to the sensory evaluation, noodles prepared with different water contents were not significantly different. According to the results, semidried noodles have development potential to complement the disadvantages of both wet noodles and dry noodles.